AUDIO GAMES TERHADAP KETERAMPILAN MENGETIK PESERTA DIDIK TUNANETRA - TRIA OKTARINDA, RATIH (Jurnal Pendidikan Khusus, 2016)
ABSTRACT A typing skill involved finger position mastery to the keyboard. Training typing skill could be done with learning media, one of them was through audio games based voice which could be played by the blind. The purpose of this research was to describe the influence of audio games toward typing skill to the blind learners in SMPLB-A YPAB Surabaya. The technique of data collection used test method, observation, and documentation. It was then analyzed using statistic non parametric with sign test. The approach was quantitative with one group pre test post test. The sample was 6 blind learners of class IX SMPLB-A YPAB Surabaya. This research indicated there was enhancement of skill value of the blind children, in pre test the average value was 60 and in post test the value was 90. Based on the test result of statistic non parametric with sign test it was obtained Zh value was 2.04 greater than critic value α = 5% i.e. 1,96 which meant null hypothesis (Ho) was refused so that it could be concluded that “there was significant influence of audio games toward typing skill to the blind learners in SMPLB-A YPAB Surabaya.” Keywords:  audio games, typing skill